2020
DOI: 10.1021/acs.iecr.0c03115
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the Development and Transfer of Freeze-Drying Operations for the Manufacturing of Biopharmaceuticals by Model-Based Design of Experiments

Abstract: In the pharmaceutical industry, freeze-drying (also known as lyophilization) is often used to increase the shelf life of heat-sensitive biopharmaceuticals such as protein-based therapeutic drugs and vaccines. The most time-and energy-consuming step of a lyophilization process is primary drying. When a new system configuration (e.g., a new equipment, product formulation, or primary packaging) is to be tested in process development or when transferring to manufacturing facilities, one needs to characterize heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This often implies that the shelf temperature and the chamber pressure are kept constant with time 14 . Yet, several studies demonstrated the potential of optimizing the drying recipe by considering time‐varying profiles of the manipulated inputs 2–4 …”
Section: The Process and Its Knowledge‐driven Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This often implies that the shelf temperature and the chamber pressure are kept constant with time 14 . Yet, several studies demonstrated the potential of optimizing the drying recipe by considering time‐varying profiles of the manipulated inputs 2–4 …”
Section: The Process and Its Knowledge‐driven Modelmentioning
confidence: 99%
“…14 Yet, several studies demonstrated the potential of optimizing the drying recipe by considering time-varying profiles of the manipulated inputs. [2][3][4] In this study, we use the comprehensive knowledge-driven The model aims at describing the key performance indicators of the process, namely T p , _ m s , and the length of the frozen layer in the vials. As in the real equipment, the shelf temperature T s may be held constant during a lyophilization run, or changed according to a piecewise linear profile, with a maximum 1 K/min rate of change.…”
Section: The Process and Its Knowledge-driven Modelmentioning
confidence: 99%
See 1 more Smart Citation